2015
DOI: 10.1108/ijoem-09-2010-0078
|View full text |Cite
|
Sign up to set email alerts
|

Marketing issues for business-to-business firms entering emerging markets

Abstract: Purpose – The purpose of this paper is to comprehensively explore marketing issues for foreign industrial companies of large, small and medium size entering emerging markets (EMs), particularly transition economies in Eastern Europe. The vast majority of current studies about EMs focus only on defining suitable strategies related to large consumer goods corporations. Design/methodology/approach – The research adopted a multiple case stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
(62 reference statements)
1
17
1
Order By: Relevance
“…Those specificities were not confirmed in previous studies suggested by Lindgreen et al (2012) and Ulaga and Eggert (2006). This could indicate that supplier companies need to refine their management to cover those elements more effectively, and corroborates with Cassia and Magno (2015) with regard to the companies directing their efforts to achieving a higher addition of value in a B2B context.…”
Section: Figure 1 Predominant Elements Identified By Companies Invescontrasting
confidence: 45%
See 1 more Smart Citation
“…Those specificities were not confirmed in previous studies suggested by Lindgreen et al (2012) and Ulaga and Eggert (2006). This could indicate that supplier companies need to refine their management to cover those elements more effectively, and corroborates with Cassia and Magno (2015) with regard to the companies directing their efforts to achieving a higher addition of value in a B2B context.…”
Section: Figure 1 Predominant Elements Identified By Companies Invescontrasting
confidence: 45%
“…In terms of opportunity, Cassia and Magno (2015) highlight that emerging countries are generating a wide range of opportunities for B2B relationships. The authors mention that scientific studies on this context (B2B) should be reinforced since most of the research focuses mainly on business-to-consumer industries.…”
Section: Introductionmentioning
confidence: 99%
“…Others posit weak intellectual property rights protection systems (Sartor andBeamish, 2014, Li and as a definitional element of EMs. Many authors conclude that a crucial feature of EMs is inefficient and/or corrupt legal as well administrative systems that all together contributes to a higher cost of doing business (Estrin et al, 2008, Diaz Hermelo and Vassolo, 2012, Chen and Yu, 2012, Li et al, 2014a, Wu and Chen, 2014, Gaur et al, 2014, Cassia and Magno, 2015.…”
Section: Institutional Differencesmentioning
confidence: 99%
“…Institutional Voids and Differences (Marano et al, 2017, Meyer and Peng, 2016, Ma et al, 2016, Li and Oh, 2016, Kirca et al, 2016, Shirodkar and Mohr, 2015, Liao, 2015, Deng and Yang, 2015, Cassia and Magno, 2015, Anderson and Sutherland, 2015, Agnihotri and Bhattacharya, 2015, Gaur et al, 2014, Wu and Chen, 2014, Tuschke et al, 2014, Sartor and Beamish, 2014, Sandberg, 2014, Li et al, 2014b…”
Section: Institutionalmentioning
confidence: 99%
“…But MT practices in emerging markets (EMs) could be a difficult task, because these contexts are subject to institutional turbulence, complexity and within-country diversity (Burgess & Steenkamp, 2006). Cassia and Magno (2015) recognize institutional uncertainty, difficulties in building a sales network and inability to adapt as three major problems in marketing in EMs. Combined with credence attributes, MT marketing in EMs thus becomes a difficult task for service providers.…”
Section: Introductionmentioning
confidence: 99%